건강 상태와 약물오남용 행위 사이에서 자기효능감의 매개효과 - 박경래; 장하영; Park, Kyung Lae; Jang, Ha Young (한국임상약학회지, 2018)
Background: The appropriate use of drugs is very important for a healthy life, as appropriate medication must be taken correctly for successful treatment of a disease. The purpose of this study was to investigate the self-efficacy between health status and drug abuse behavior. Methods: The subjects of this study were selected from 15 workshops located in Seoul, Incheon, Daejeon, and Chungnam, and, convenience sampling was conducted for each employee between September, 2017 and October 2017. A total of 204 questionnaires were analyzed. The questions evaluated health status, self-efficacy, drug abuse behavior, and general characteristics. Results: First, there was no difference in health status according to the general characteristics of the subjects. The self-efficacy varied according to gender, educational background, and monthly income, but not by marital status and residence area. In addition, drug abuse behaviors differed according to gender, residence area, and monthly income, but not by marital status and education level. Second, drug abuse behavior negatively correlated with health status and self-efficacy. Third, regression analysis showed that the self-efficacy between the health status and drug abuse behavior had a partially mediating effect. Conclusion: In patients with poor health status, it is necessary to increase their self-efficacy to reduce reduce drug abuse. Therefore, regular education programs targeting efficacy and drug knowledge are required in the community.